Converse nonimplication

From HandWiki
Short description: Logical connective
Venn diagram of [math]\displaystyle{ P \nleftarrow Q }[/math]
(the red area is true)

In logic, converse nonimplication[1] is a logical connective which is the negation of converse implication (equivalently, the negation of the converse of implication).

Definition

Converse nonimplication is notated [math]\displaystyle{ P \nleftarrow Q }[/math], or [math]\displaystyle{ P \not \subset Q }[/math], and is logically equivalent to [math]\displaystyle{ \neg (P \leftarrow Q) }[/math] and [math]\displaystyle{ \neg P \wedge Q }[/math].

Truth table

The truth table of [math]\displaystyle{ P \nleftarrow Q }[/math].[2]

[math]\displaystyle{ P }[/math] [math]\displaystyle{ Q }[/math] [math]\displaystyle{ P \nleftarrow Q }[/math]
True True False
True False False
False True True
False False False

Notation

Converse nonimplication is notated [math]\displaystyle{ p \nleftarrow q }[/math], which is the left arrow from converse implication ([math]\displaystyle{ \leftarrow }[/math]), negated with a stroke (/).

Alternatives include

  • [math]\displaystyle{ p \not\subset q }[/math], which combines converse implication's [math]\displaystyle{ \subset }[/math], negated with a stroke (/).
  • [math]\displaystyle{ p \tilde{\leftarrow} q }[/math], which combines converse implication's left arrow ([math]\displaystyle{ \leftarrow }[/math]) with negation's tilde ([math]\displaystyle{ \sim }[/math]).
  • Mpq, in Bocheński notation

Properties

falsehood-preserving: The interpretation under which all variables are assigned a truth value of 'false' produces a truth value of 'false' as a result of converse nonimplication

Natural language

Grammatical

Example,

If it rains (P) then I get wet (Q), just because I am wet (Q) does not mean it is raining, in reality I went to a pool party with the co-ed staff, in my clothes (~P) and that is why I am facilitating this lecture in this state (Q).

Rhetorical

Q does not imply P.

Colloquial

Boolean algebra

Converse Nonimplication in a general Boolean algebra is defined as [math]\displaystyle{ q \nleftarrow p=q'p }[/math].

Example of a 2-element Boolean algebra: the 2 elements {0,1} with 0 as zero and 1 as unity element, operators [math]\displaystyle{ \sim }[/math] as complement operator, [math]\displaystyle{ \vee }[/math] as join operator and [math]\displaystyle{ \wedge }[/math] as meet operator, build the Boolean algebra of propositional logic.

[math]\displaystyle{ {}\sim x }[/math] 1 0
x 0 1
and
y
1 1 1
0 0 1
[math]\displaystyle{ y_\vee x }[/math] 0 1 x
and
y
1 0 1
0 0 0
[math]\displaystyle{ y_\wedge x }[/math] 0 1 x
then [math]\displaystyle{ \scriptstyle{y \nleftarrow x}\! }[/math] means
y
1 0 0
0 0 1
[math]\displaystyle{ \scriptstyle{y \nleftarrow x}\! }[/math] 0 1 x
(Negation) (Inclusive or) (And) (Converse nonimplication)

Example of a 4-element Boolean algebra: the 4 divisors {1,2,3,6} of 6 with 1 as zero and 6 as unity element, operators [math]\displaystyle{ \scriptstyle{ ^{c}}\! }[/math] (co-divisor of 6) as complement operator, [math]\displaystyle{ \scriptstyle{_\vee}\! }[/math] (least common multiple) as join operator and [math]\displaystyle{ \scriptstyle{_\wedge}\! }[/math] (greatest common divisor) as meet operator, build a Boolean algebra.

[math]\displaystyle{ \scriptstyle{x^c}\! }[/math] 6 3 2 1
x 1 2 3 6
and
y
6 6 6 6 6
3 3 6 3 6
2 2 2 6 6
1 1 2 3 6
[math]\displaystyle{ \scriptstyle{y_\vee x}\! }[/math] 1 2 3 6 x
and
y
6 1 2 3 6
3 1 1 3 3
2 1 2 1 2
1 1 1 1 1
[math]\displaystyle{ \scriptstyle{y_\wedge x} }[/math] 1 2 3 6 x
then [math]\displaystyle{ \scriptstyle{y \nleftarrow x}\! }[/math] means
y
6 1 1 1 1
3 1 2 1 2
2 1 1 3 3
1 1 2 3 6
[math]\displaystyle{ \scriptstyle{y \nleftarrow x}\! }[/math] 1 2 3 6 x
(Co-divisor 6) (Least common multiple) (Greatest common divisor) (x's greatest divisor coprime with y)

Properties

Non-associative

[math]\displaystyle{ r \nleftarrow (q \nleftarrow p) = (r \nleftarrow q) \nleftarrow p }[/math] if and only if [math]\displaystyle{ rp = 0 }[/math] #s5 (In a two-element Boolean algebra the latter condition is reduced to [math]\displaystyle{ r = 0 }[/math] or [math]\displaystyle{ p=0 }[/math]). Hence in a nontrivial Boolean algebra Converse Nonimplication is nonassociative. [math]\displaystyle{ \begin{align} (r \nleftarrow q) \nleftarrow p &= r'q \nleftarrow p & \text{(by definition)} \\ &= (r'q)'p & \text{(by definition)} \\ &= (r + q')p & \text{(De Morgan's laws)} \\ &= (r + r'q')p & \text{(Absorption law)} \\ &= rp + r'q'p \\ &= rp + r'(q \nleftarrow p) & \text{(by definition)} \\ &= rp + r \nleftarrow (q \nleftarrow p) & \text{(by definition)} \\ \end{align} }[/math]

Clearly, it is associative if and only if [math]\displaystyle{ rp=0 }[/math].

Non-commutative

  • [math]\displaystyle{ q \nleftarrow p=p \nleftarrow q }[/math] if and only if [math]\displaystyle{ q = p }[/math] #s6. Hence Converse Nonimplication is noncommutative.

Neutral and absorbing elements

  • 0 is a left neutral element ([math]\displaystyle{ 0 \nleftarrow p=p }[/math]) and a right absorbing element ([math]\displaystyle{ {p \nleftarrow 0=0} }[/math]).
  • [math]\displaystyle{ 1 \nleftarrow p=0 }[/math], [math]\displaystyle{ p \nleftarrow 1=p' }[/math], and [math]\displaystyle{ p \nleftarrow p=0 }[/math].
  • Implication [math]\displaystyle{ q \rightarrow p }[/math] is the dual of converse nonimplication [math]\displaystyle{ q \nleftarrow p }[/math] #s7.

Converse Nonimplication is noncommutative
Step Make use of Resulting in
s.1 Definition [math]\displaystyle{ \scriptstyle{q\tilde{\leftarrow}p=q'p\,}\! }[/math]
s.2 Definition [math]\displaystyle{ \scriptstyle{p\tilde{\leftarrow}q=p'q\,}\! }[/math]
s.3 s.1 s.2 [math]\displaystyle{ \scriptstyle{q\tilde{\leftarrow}p=p\tilde{\leftarrow}q\ \Leftrightarrow\ q'p=qp'\,}\! }[/math]
s.4 [math]\displaystyle{ \scriptstyle{q\,}\! }[/math] [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] [math]\displaystyle{ \scriptstyle{q.1\,}\! }[/math]
s.5 s.4.right - expand Unit element [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] [math]\displaystyle{ \scriptstyle{q.(p+p')\,}\! }[/math]
s.6 s.5.right - evaluate expression [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] [math]\displaystyle{ \scriptstyle{qp+qp'\,}\! }[/math]
s.7 s.4.left = s.6.right [math]\displaystyle{ \scriptstyle{q=qp+qp'\,}\! }[/math]
s.8 [math]\displaystyle{ \scriptstyle{q'p=qp'\,}\! }[/math] [math]\displaystyle{ \scriptstyle{\Rightarrow\,}\! }[/math] [math]\displaystyle{ \scriptstyle{qp+qp'=qp+q'p\,}\! }[/math]
s.9 s.8 - regroup common factors [math]\displaystyle{ \scriptstyle{\Rightarrow\,}\! }[/math] [math]\displaystyle{ \scriptstyle{q.(p+p')=(q+q').p\,}\! }[/math]
s.10 s.9 - join of complements equals unity [math]\displaystyle{ \scriptstyle{\Rightarrow\,}\! }[/math] [math]\displaystyle{ \scriptstyle{q.1=1.p\,}\! }[/math]
s.11 s.10.right - evaluate expression [math]\displaystyle{ \scriptstyle{\Rightarrow\,}\! }[/math] [math]\displaystyle{ \scriptstyle{q=p\,}\! }[/math]
s.12 s.8 s.11 [math]\displaystyle{ \scriptstyle{q'p=qp'\ \Rightarrow\ q=p\,}\! }[/math]
s.13 [math]\displaystyle{ \scriptstyle{q=p\ \Rightarrow\ q'p=qp'\,}\! }[/math]
s.14 s.12 s.13 [math]\displaystyle{ \scriptstyle{q=p\ \Leftrightarrow\ q'p=qp'\,}\! }[/math]
s.15 s.3 s.14 [math]\displaystyle{ \scriptstyle{q\tilde{\leftarrow}p=p\tilde{\leftarrow}q\ \Leftrightarrow\ q=p\,}\! }[/math]

Implication is the dual of Converse Nonimplication
Step Make use of Resulting in
s.1 Definition [math]\displaystyle{ \scriptstyle{\operatorname{dual}(q\tilde{\leftarrow}p)\,}\! }[/math] [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] [math]\displaystyle{ \scriptstyle{\operatorname{dual}(q'p)\,}\! }[/math]
s.2 s.1.right - .'s dual is + [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] [math]\displaystyle{ \scriptstyle{q'+p\,}\! }[/math]
s.3 s.2.right - Involution complement [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] [math]\displaystyle{ \scriptstyle{(q'+p)''\,}\! }[/math]
s.4 s.3.right - De Morgan's laws applied once [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] [math]\displaystyle{ \scriptstyle{(qp')'\,}\! }[/math]
s.5 s.4.right - Commutative law [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] [math]\displaystyle{ \scriptstyle{(p'q)'\,}\! }[/math]
s.6 s.5.right [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] [math]\displaystyle{ \scriptstyle{(p\tilde{\leftarrow}q)'\,}\! }[/math]
s.7 s.6.right [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] [math]\displaystyle{ \scriptstyle{p\leftarrow q\,}\! }[/math]
s.8 s.7.right [math]\displaystyle{ \scriptstyle{=\,}\! }[/math] [math]\displaystyle{ \scriptstyle{q\rightarrow p\,}\! }[/math]
s.9 s.1.left = s.8.right [math]\displaystyle{ \scriptstyle{\operatorname{dual}(q\tilde{\leftarrow}p)=q\rightarrow p\,}\! }[/math]

Computer science

An example for converse nonimplication in computer science can be found when performing a right outer join on a set of tables from a database, if records not matching the join-condition from the "left" table are being excluded.[3]

References

External links